Destination image: perspectives of tourists vs. residents - Agapito, Dora (2014)
This study aims to measure the image of Lagos in the Algarve region, the most important Portuguese destination, using a cognitive, affective and behavioral approach. Given the lack of studies which compare the perspectives of tourists and residents, the empirical investigation includes a mixed methodology enabling a holistic approach followed by a quantitative methodology with the use of questionnaires for both tourists and residents. The attributes that are more consensually associated with Lagos are the good weather and good beaches, although these variables do not have significant discriminatory power for "recommendation of the destination to friends and family" as the dependent variable.